Anti-proliferative and pro-apoptotic effects of curcumin on skin cutaneous melanoma: Bioinformatics analysis and in vitro experimental studies - Li, Long; Lu, Shuwen; Ma, Chao (Frontiers in Genetics, 2022)
Objective: To reveal the potential mechanisms of curcumin for the treatment of skin cutaneous melanoma (SKCM) and its identify novel prognostic biomarkers. Methods: We searched the Cancer Genome Atlas and Traditional Chinese Medicine Systems Pharmacology database for the data on SKCM and curcumin. We conducted data analysis using R and online tools. The propagation and migration of SKCM cells were assessed with CCK-8 and scratch wound assays, respectively. We assessed apoptosis by TUNEL assay and western blot. Results: The survival analysis revealed that the mRNA expressions of DPYD, DPYS, LYN, PRKCQ, and TLR1 were significantly related to a favorable overall survival in SKCM patients. Additionally, the mRNA expression level of DPYD was associated with GPI, LYN, PCSK9, PRKCQ, and TLR1 mRNAs. GSEA results showed that the prognostic hub genes were augmented with ultraviolet, apoptosis, and metastasis. Curcumin expressed proliferation and migration of SK-MEL-1 cells (P < 0.05), and induced apoptosis (P < 0.05) significantly. Conclusion: Curcumin may have potential therapeutic effects in SKCM by inhibiting cell proliferation and migration and inducing apoptosis by regulating oxygen-related signaling pathways. The hub genes might be identified as novel biomarkers for SKCM.